Graphene prepared by gamma irradiation for corrosion protection of stainless steel 316 in chloride containing electrolytes1. Issue 88 (25th September 2015) - Atta, Nada F.; Amin, Khaled M.; Abd El-Rehim, Hassan A.; Galal, Ahmed
<x xml:space="preserve">Abstract</x> Graphene prepared by gamma irradiation of GO and used as a coating against pitting corrosion of AISI 316 in NaCl.